The Costs and Benefits of Investing in Universal Preschool: Evidence From a Spanish Reform. Issue 3 (20th November 2017) - van Huizen, Thomas; Dumhs, Lisa; Plantenga, Janneke
Abstract : This study provides a cost–benefit analysis of expanding access to universal preschool education, focusing on a Spanish reform that lowered the age of eligibility for publicly provided universal preschool from age 4 to age 3. Benefits in terms of child development and maternal employment are estimated using evidence on the causal effects of this reform. In the baseline estimation the benefit–cost ratio is over 4, indicating sizeable net societal benefits of the preschool investment. The results show that the child development effects are the major determinant of the cost–benefit ratio; the employment gains for parents appear to play a relatively minor role. Overall, the cost–benefit analysis provides support for investing in high‐quality preschool education.